2015
DOI: 10.1063/1.4934578
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced enhanced polarization in multilayer BiFeO3/BaTiO3 structure with improved energy storage properties

Abstract: Present work reports the fabrication of a multilayer (5-layer) structure of BiFeO3(BFO)/BaTiO3(BTO) using spin-coating technique. The crystallographic structure, surface morphology and ferroelectric behavior of multilayer structure in metal-ferroelectric-metal capacitor have been studied. Le-Bail refinement of X-ray diffraction data revealed the formation of polycrystalline pure perovskite phase with induced stress. The values of remnant (Pr) and saturation polarization (Ps) for BFO/BTO multilayer structure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In our work, we found that BiFeO 3 containing small amounts of Bi 2 Fe 4 O 9 shows a better photocatalytic activity and photoelectric performance than that of pure BiFeO 3 . However, although some researchers had reported the visible-light-driven photodegradation activities of BiFeO 3 /Bi 2 Fe 4 O 9 microspheres until now, there has been little report on its photocatalytic hydrogen evolution from water, and the photoelectric performance and photoreactive mechanism of BiFeO 3 /Bi 2 Fe 4 O 9 heterojunctions still need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In our work, we found that BiFeO 3 containing small amounts of Bi 2 Fe 4 O 9 shows a better photocatalytic activity and photoelectric performance than that of pure BiFeO 3 . However, although some researchers had reported the visible-light-driven photodegradation activities of BiFeO 3 /Bi 2 Fe 4 O 9 microspheres until now, there has been little report on its photocatalytic hydrogen evolution from water, and the photoelectric performance and photoreactive mechanism of BiFeO 3 /Bi 2 Fe 4 O 9 heterojunctions still need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic capacitors have been used for energy storage purposes for more than 60 years, which has a vital role in the field of power electronics and pulsed power systems due to their small footprint, excellent temperature stability (up to 250 °C) and high ε r . [ 35 , 89 , 112 , 113 , 114 , 115 , 116 ] It is well known that the capacity of a capacitor is inversely proportional to the distance between the electrodes and directly proportional to the area of the electrodes. Therefore, those ceramic dielectrics that are made into a multilayer structure can obtain a larger capacitance capacity.…”
Section: Superiority Of Multilayer Structure Dielectric For Energy Storagementioning
confidence: 99%
“…As an effective approach, stress/strain engineering has been generally employed to regulate the microstructures [27,28] and properties of ferroelectric materials, such as ferroelectricity, [29][30][31][32] piezoelectricity, [33][34][35][36] energy-storage performance, [37][38][39] and ECE. [16,[40][41][42][43][44] Considering the practical application, the cooling temperature range of the ECE is mainly expected to be around room temperature.…”
Section: Introductionmentioning
confidence: 99%